Eksplorasi Praktik Tadabur Al-Qur’an dalam Pembelajaran Pendidikan Agama Islam di Jenjang Sekolah Menengah Pertama - Aulia, Muhammad Hizba; Kosasih, Aceng; Firmansyah, Mokh. Iman (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aims to explore Qur’anic tadabur practices in Islamic Religious Education (IRE), particularly within the Qur’an–Hadith component at the junior high school level. IRE learning continues to be dominated by technical and procedural approaches that emphasize reading and memorization, which have not yet fully encouraged students’ reflective engagement with and internalization of the Qur’an’s messages. This study employed a qualitative approach with a phenomenological design through in-depth interviews with 10 IRE teachers and 10 students, supported by limited contextual observations and the analysis of instructional documents and learning materials from State Junior High School 1 Bandung, State Junior High School 5 Bandung, and State Junior High School 7 Bandung, Indonesia. The data were analyzed using the interactive data analysis model proposed by Miles and Huberman, including data reduction, data display, and reflective and continuous conclusion drawing and verification. The findings indicate that Qur’anic literacy in IRE learning is predominantly practiced in a textual and procedural manner and has not yet been integrated with tadabur as a reflective learning experience. Consequently, the internalization of religious values tends to occur instructionally and has not fully developed into students’ personal religious awareness. These findings highlight the importance of strengthening contextual and reflective Qur’an–Hadith learning to position tadabur as a meaningful pedagogical experience that supports the sustainable formation of students’ religious character.